Pengaruh Aplikasi Bakteri Fotosintesis dengan Pupuk Kimia terhadap Produktivitas Cabai Rawit (Capsicum frutescens L.) - ., Nadzifatin; Furoidah, Nanik (JURNAL AGROPLANT, 2023)
The purpose of this study was to examine the effect of the application of photosynthetic bacteria with chemical fertilizers on the productivity of cayenne pepper. The research was conducted in Pancakarya Village, Ajung District, Jember Regency from September to December 2022 with an altitude of 50 meters above sea level. This study used a non factoria randomized block design (RAK) with six treatments and four replications for a total of twenty four plants. The treatments observed were P0 = control; P1 = 5 ml/L PSB; P2 = 5 ml/L PSB and 2 g NPKCaMg fertilizers (16:16;16:6:0,5); P3 = 5 ml/L PSB and 2 g NPKSCaMg fertilizers (20:4:4:18:1:1); P4 = 5 ml/L PSB and 2 g NPKSCaMg fertilizers (17:12:12:6:4:2); P5 = 5 ml/L PSB and 2 g NPKSCaMg fertilizers (20:30:23:2:3:2). The results showed that the administration of a single application of photosynthetic bacteria did not have a significant effect on all observed parameters. The application of 5 ml/L PSB and 2 g NPKSCaMg fertilizers (20:4:4:18:1:1) had the best effect on stem diameter (7,63 mm), fruit weight planted (52,7 g) and number of fruit planted (25,5 fruit). Give a significant effect on the increase in fruit diameter (12,2 mm) from the control plant (8,1 mm).